Integration of care for HIV and opioid use disorder. (1st April 2019) - Oldfield, Benjamin J.; Muñoz, Nicolas; McGovern, Mark P.; Funaro, Melissa; Villanueva, Merceditas; Tetrault, Jeanette M.; Edelman, E. Jennifer
Abstract : Objective: We sought to identify optimal strategies for integrating HIV- and opioid use disorder-(OUD) screening and treatment in diverse settings. Design: Systematic review. Methods: We searched Ovid MEDLINE, PubMed, Embase, PsycINFO and preidentified websites. Studies were included if they were published in English on or after 2002 through May 2017, and evaluated interventions that integrated, at an organizational level, screening and/or treatment for HIV and OUD in any care setting in any country. Results: Twenty-nine articles met criteria for inclusion, including 23 unique studies: six took place in HIV care settings, 12 in opioid treatment settings, and five elsewhere. Eight involved screening strategies, 22 involved treatment strategies, and seven involved strategies that encompassed screening and treatment. Randomized controlled studies demonstrated low-to-moderate risk of bias and observational studies demonstrated fair to good quality. Studies in HIV care settings ( n  = 6) identified HIV-related and OUD-related clinical benefits with the use of buprenorphine/naloxone for OUD. No studies in HIV care settings focused on screening for OUD. Studies in opioid treatment settings ( n  = 12) identified improving HIV screening uptake and clinical benefits with antiretroviral therapy when provided on-site. Counseling intensity for OUD medication adherence or HIV-related risk reduction was not associated with clinical benefits. Conclusion: Screening for HIV can be effectively delivered in opioid treatment settings, yet there is a need to identify optimal OUD screening strategies in HIV care settings. Strategies integrating the provision of medications for HIV and for OUD should be expanded and should not be contingent on resources available for behavioral interventions. Registration: A protocol for record eligibility was developed a priori and was registered in the PROSPERO database of systematic reviews (registration number CRD42017069314). Abstract : Supplemental Digital Content is available in the text